2007
DOI: 10.1111/j.1530-0277.2007.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the Extended Amygdala in C57BL/6J Mice Do Not Block the Intermittent Ethanol Vapor‐Induced Increase in Ethanol Consumption

Abstract: The results obtained clearly demonstrate that the cEA has a role in the regulation of ethanol consumption in the limited-access procedure. However, neither lesions of the CeA nor BNSTLP prevented the intermittent ethanol vapor-induced increase in consumption. These data do not preclude some role of the cEA in the increased ethanol consumption following intermittent ethanol vapor exposure, but would suggest that other brain regions also must have a significant influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 34 publications
(47 reference statements)
12
55
0
Order By: Relevance
“…This level of increased ethanol consumption attained in the present series of experiments has been previously shown to result in significant elevation (two-to threefold increase) in blood ethanol levels and brain ethanol concentrations (Griffin et al, 2009b). These results (increased alcohol consumption) are congruent with those reported by others using similar procedures in mice (Finn et al, 2007;Dhaher et al, 2008) and rats (Gehlert et al, 2007;Roberts et al, 1996;Roberts et al, 2000;Sommer et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…This level of increased ethanol consumption attained in the present series of experiments has been previously shown to result in significant elevation (two-to threefold increase) in blood ethanol levels and brain ethanol concentrations (Griffin et al, 2009b). These results (increased alcohol consumption) are congruent with those reported by others using similar procedures in mice (Finn et al, 2007;Dhaher et al, 2008) and rats (Gehlert et al, 2007;Roberts et al, 1996;Roberts et al, 2000;Sommer et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, a study identified the putamen as a significant region in the representation of action-specific values that are important for the mediation between reward and adaptive behavior (FitzGerald, Friston, & Dolan, 2012), linking reward to action (Redgrave et al, 2010), planning actions (Monchi, Ko, & Strafella, 2006), and encoding habits as opposed to goal-directed values (Wunderlich, Dayan, & Dolan, 2012) e processes that are crucial for the transition to alcohol addiction and its maintenance. The activation of the putamen was also suggested to be associated with alcohol craving (Heinz et al, 2005) and alcohol preference, via projections from the amygdala (Dhaher, Finn, Snelling, & Hitzemann, 2008;Russchen & Price, 1984). BDNF Val66Met might thus have an effect on neural correlates of processing rewarding outcomes and might in consequence modulate adaptive behavior in a rewarding context, which might turn into increased habitual problematic alcohol consumption and thus could result in increased alcohol craving and manifest as alcohol addiction.…”
Section: Discussionmentioning
confidence: 96%
“…The regions compared (nucleus accumbens shell [SH], central nucleus of the amygdala [CeA], and prelimbic cortex [PL]) are components of the addiction circuit (Koob and Volkow, 2010, 2016). A previous study (Dhaher et al, 2008) suggested that the CeA but not the SH has a more significant role in preference (2-bottle choice) consumption. The short-term selection of the High and Low ethanol preference lines from heterogeneous stock-collaborative cross (HS-CC) founders has been described elsewhere (Colville et al, 2017).…”
Section: Introductionmentioning
confidence: 92%